IMPLEMENTATION OF THE HAVERSINE METHOD FOR THE APPLICATION OF FINDING TOURIST ATTRACTIONS IN NANGGUNG DISTRICT - Fatimah, Fety; Al Ikhsan, Safaruddin Hidayat; Wulandari, Berlina (Jurnal Pilar Nusa Mandiri, 2022)
Traveling is one of the most popular hobbies nowadays. Natural tourist destinations located in the countryside are a choice for travelers. There are several tourist sites located in the country of Bogor, one of which is in the district of Nanggung. Nanggung sub-district is in the region of west Bogor, approximately 60 km from the capital city of Bogor Regency (Cibinong). The location of the Nanggung sub-district has an area of 135.25 km2, located near the foot of Mount Salak, creating a beautiful atmosphere and quite cold air. There are approximately 30 tourist destinations in the Nanggung sub-district. Base mobile application to help tourists determine the nearest destination. This mobile application helps domestic and foreign tourists select the closest tourist sites visited in Nanggung, Bogor Regency. The haversine method used to calculate the distance is the haversine method. The haversine method estimates the distance. Haversine will calculate the distance between the application user and the location of the surrounding tourist points located in the Nanggung sub-district. This study aims to calculate the length of application users to tourist sites. So that users get convenience in determining the closest location from the application user's position.